Reinado de Luzia Teresa: contos infomemoriais - Santiago, Luciana Ataíde Dias (2024)
Memory serves as the vibrant substance of oral literature. Luzia Teresa dos Santos, a storyteller of folk tales hailing from Guarabira, Paraíba, born in the early 20th century, encapsulates within her memory the stories acquired during childhood, depicting the fantastical world of late 19th and early 20th-century human experiences. This research focuses on the folk tales narrated by Luzia Teresa, aiming to construct the literary-cultural and social pathways of the protagonist narrator, based on the mnemonic traces vestiges contained within her folk tales and in informational devices that talk about the work and trajectory of Luzia Teresa.The study analyzes the mnemonic traces present in the narrator's tales, archived in the Research and Documentation Center for Popular Culture (NUPPO) at the Federal University of Paraíba (UFPB), comprising 242 folk tales. Employing a qualitative approach combined with documentary and bibliographic research. To deepen the corpus, the arqueciário approach was used, which combines the archaeological method to delve into the margins, the threshold between the real and the oneiric, the unsaid, and the concealed utterances, along with the indicial method, seeking mnemonic traces with sensitivity for discerning their viability. The inquiry revolves around identifying the mnemonic traces vestiges within Luzia Teresa's folk tales and elucidating their singularity. Theoretical dialogues encompass works by Assmann, Benjamin, Candau, Foucault, Le Goff, among others. This research aims to demonstrate that Luzia Teresa's folk tales, reflecting centuries of reinterpretations, imbued with social elements and unique authorial traits of the storyteller, serve as memorial territories of both the real and the fantastical worlds, encapsulating mnemonic traces vestiges within their scope.We indicate that, given the importance of the accountant in popular culture, in the area of Memory and Information, that the documents contained in NUPPO, which deal with her person, can be included in a unique space, dedicated only to her collection, with appropriate archival treatment. In this regard it seeks to establish the significant relevance of folk tales within the context of social information, effectively contributing to the field of Information Science and decisively impacting memory studies.